Investigation of skin infection frequency in Turkish wrestlers - Kaynar, Ömer; Engin, Ragip Ismail; Dagdeviren, Fikret; Yilmaz, Mikail; Ozkan, Bora; Ozturk, Sadik (TURKISH SOC DERMATOLOGY VENEROLOGY, 2017)
Background and Design: The aim of this study was to determine the frequency of dermatological infections among Turkish wrestlers. Materials and Methods: We included 202 wrestlers from different regions of Turkey who volunteered to participate in the study. The "Athlete Biography and Dermatologic Examination Findings" survey that was designed before the research was completed during dermatological examination and dermatologic findings of each athlete were evaluated. Results: During the physical examination of 202 Turkish wrestlers, 115 (57%) of participants were observed to have skin infection while no skin infection was found in 87 (43%). It has been detected that these infections were fungal, bacterial and viral in 31%, 18% and 8% of patients, respectively. The rates of infections were 25 (12%), 28 (14%), 15 (8%), 12 (6%), 12 (6%), 8 (4%), 6 (3%), 5 (2%), 2 (1%), and 2 (1%) for tinea corporis, tinea pedis, erythrasma, folliculitis, wart, onychomycosis, paronychia, herpes, impetigo, and tinea versicolor, respectively. Conclusion: In this study, it was found that Turkish wrestlers had skin infections, these infections were not as common as reported in the literature. It can be understood that early diagnosis and treatment is very important in reducing the prevalence of these infections in wrestlers.
Keywords: Sport; wrestling; skin infections